P47 Post-Operative Oxygen Saturation, Prescribing & Administration in Patients Undergoing Elective Orthopaedic Surgery. (19th November 2012) - Hogan, AM; Anand, E; Oddy, MJ; Welch, J; Booth, H
Abstract : Introduction: There is increasing interest in maximising perioperative care of surgical patients, including response to oxygen desaturation which may occur in association with anaesthesia, analgesic/sedative drugs, and/or indicate pathology. There is thus potentially great importance in understanding the incidence and profile of oxygen desaturation in the post-operative patient, and documenting our response to it. Methods: We recorded sequential SpO2 values and oxygen prescription/administration from the charts of 65 patients (mean age 56.5 years ( SD 20.2), BMI 29.6 (10.5), 38 Females) admitted to University College London Hospital for elective orthopaedic surgery, starting at point of transfer from recovery room to ward. Nine were current smokers, one patient had COPD, and eight had possible sleep apnoea. None used home oxygen or CPAP and all were normoxic pre-operatively. Results: One-third (30.8%; 20/65) of patients experienced an isolated, minor desaturation event (Figure 1 ): mean minimum SpO2 91.9% ( SD 2.2). 'Desaturators' were older ( P =0.038) but not 'sicker' compared to those who remained normoxic, determined by smoking status and ASA grade, and by post-operative rate of chest x-ray request, blood transfusion, and antibiotic requirement. Thus, the majority of desaturations were minor and of limited clinical significance; in a few cases perhaps representing spurious values. Recurrent (>/= 3 desaturations/24 hours) with/without more serious desaturations (<90% SpO2 ) occurred in 6.2% (4/65). Oxygen was prescribed for only one-third of patients (35.4%; 23/65), but was administered to three-quarters (75.4%; 49/65) typically as a gradual 'down-titration' of high-flows given in recovery rather than in response to desaturation. Some patients remained on oxygen despite sequential SpO2 values of 100%. Strong opiates were frequently prescribed (93.8%; 61/65), sometimes with night sedation (9.2%; 6.65). Comment: British Thoracic Society national guidelines encourage oxygen administration titrated to SpO2, but we show that this aim may not currently be fully realized in surgical patients, perhaps partly due to lack of routine oxygen prescribing. Encouragement of early oxygen prescribing by surgeons and anaethetists, who already routinely prescribe thrombo-prophylaxis, prophylactic antibiotics and analgesia, might help to ensure that patients are set-up for better matching of oxygen administration to need for the duration of their post-operative recovery.